El código del trabajo frente a las enfermedades profesionales ocasionadas por el teletrabajo - Cisneros-Zúñiga, Cinthya Paulina; Jiménez-Martínez, Roberto Carlos; Correa-Cepeda, Paola Alejandra; Fuenmayor-Cuadrado, Johnny Esteban (IUSTITIA SOCIALIS, 2021)
El código del trabajo frente a las enfermedades profesionales ocasionadas por el teletrabajo